Etnografi Pala: Telaah Makna pada Masyarakat Wawonii di Tondonggito - Hadrianti, Rezky; Winesty Sofiani, Wa Ode; Al Kausar, Muhamad (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2025)
This research aims to determine the meaning of the nutmeg plant for the lives of the Wawonii people in Tondonggito Village, Southeast Wawonii District, Konawe Islands Regency, Southeast Sulawesi Province. This research uses the theory of meaning according to Spradley (1997) that to know meaning you must first know the uses of an object. The method used to collect data uses ethnographic methods, because it emphasizes participant observation techniques and in-depth interviews. The data analysis technique used in the research is descriptive qualitative.The results of the research show that the Wawonii people in Tondonggito Village, Southeast Wawonii District, Konawe Islands Regency, Southeast Sulawesi Province have been familiar with the nutmeg plant for quite a long time. In the view of the local community, the nutmeg plant is very meaningful because this plant is multipurpose. People in this village have used parts of the nutmeg plant for generations. Practices for using the nutmeg plant include it as a spice, an ingredient for making pickles and sweets, fertilizer, medicine, an ingredient for cold powder (burampae), firewood, copra house poles (para-para), and as a garden fence.